Strategy for the Development of Micro, Small and Medium-sized Enterprises (MSMEs) Based on Collaborative Governance in South Tapanuli - Aida Mahrani Siregar; Darwis Harahap; Rukiah Lubis (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2026)
This study aims to analyze the development strategy of Micro, Small, and Medium Enterprises (MSMEs) based on collaborative governance in South Tapanuli Regency. The study employed a qualitative approach, with data collected through observations, interviews, and documentation. The research informants consisted of MSME owners, PT Agincourt Resources, Bagas Silua, the Department of Trade and Cooperatives for MSMEs, and the Department of Investment and One-Stop Integrated Services. The findings indicate that MSME development is significantly influenced by collaboration among the government, the private sector, and MSME actors. The government plays a vital role in facilitating business legalization, providing guidance, training, and mentoring, while the private sector contributes to capacity building and product marketing. Internal factors, such as managerial capability, creativity, and entrepreneurial independence, as well as external factors, including policy support, training programs, and strategic partnerships, also affect the success of MSMEs. The collaborative governance model, implemented through cross-sectoral coordination and the active involvement of MSME stakeholders, has proven effective in enhancing business capacity, improving competitiveness, and increasing the contribution of MSMEs to local economic growth in South Tapanuli Regency.